Prediction of severity of acute pancreatitis using neutrophil to lymphocyte ratio - Shrestha, Ashish; Pradhananga, Smeena; Shakya, Niliza (International Surgery Journal, 2024)
Background: Patients with mild acute pancreatitis (AP) have mortality rates of less than 1% which increases up to 10% to 30% in severe AP (SAP). Early prediction of severity helps in complication prevention. Neutrophil lymphocyte ratio (NLR) could be simple, easy and cheap tool for predicting severity of AP in its early course. Methods: This prospective, observational study included forty-five patients admitted over a period of six months from August 2020 to January 2021 with diagnosis of AP at Bir hospital. NLR was performed at the time of admission. Results: The 22.2% patients had SAP with mean age of 45.6±14.73. It was common in male (60%) and the most common cause was gallstone. Etiology, BMI, neutrophilia, lymphopenia, SIRS scores were found to have statistically significant association to severity of AP. A cut off value of 4.49 was calculated for NLR for predicting severity of pancreatitis with sensitivity of 100%, specificity of 97.1%, PPV of 90.9 % and NPV of 100%. Mean NLR was 7.80±1.69 for mortality group. Conclusions: NLR can be used as a simple, easy and inexpensive prognostic marker of severity of AP.